NMR structural analysis of vascular endothelial growth factor in complex with a phage-derived peptide antagonist. Issue 2 (2003) - Pan Pan, Borlan Borlan; Fairbrother Fairbrother, Wayne J. Wayne J.
Abstract : Vascular endothelial growth factor (VEGF) is a covalently linked homodimeric protein that functions as an endothelial cell-specific mitogen, and is an important mediator of pathological angiogenesis. Phage display has been used to select three different classes of novel disulfide-constrained peptides that bind to VEGF and disrupt receptor binding with IC50 values between 0.2–10 µM. Mapping of peptide induced nuclear magnetic resonance (NMR) chemical shift changes shows that they target a region of the VEGF receptor-binding domain that overlaps with the contact surfaces of the receptors, Flt-1 and KDR. The structure of one of these 28-kDa VEGF/peptide complexes was determined by NMR spectroscopy. The structure is based on a total of 4416 internuclear distance and dihedral angle restraints derived from data obtained using samples of the complex containing either 13 C/ 15 N-labeled peptide or protein. Incorporation of residual dipolar coupling restraints improved both the precision and accuracy of the structure (as judged by comparison with crystal structures of VEGF). Comparison with the structure of a different VEGF/peptide complex reveals different peptide binding modes that each resemble those of natural protein ligands (an anti-VEGF antibody and the VEGF-receptor Flt-1). Prospects for the development of small-molecule antagonists of VEGF, based on the VEGF-bound peptide structures, are discussed.